The transformation of MESS & TISK from foundation to 2005: "a story of rejoicing" - Yeşilbağ, Melih. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2008., 2008)
This thesis scrutinizes the history of MESS and TISK, two representative organizations of big capital in Turkey from 1960s to 2005. Based on a discursive analysis of the publications of these organizations, it traces the changing mood of the capitalist class in social and political realms as well as in the area of industrial relations. Due to strong unionization and rising worker militancy, the associations were socially timid, ineffective in the political arena and unable to develop a strategy to confront the labor movement in the pre-1980 period. The military intervention in 1980, however, turned the power balance between capital and labor. This process lent the capitalist class a considerable social legitimacy and self-confidence. From 1980 to 2005, the associations enhanced their social prestige by increasing their cultural and social capital, augmented their political strength by developing closer ties with state officials and party leaders and enjoyed their superiority over labor unions that were seriously weakened by the new labor laws. The essential feature of this period is the fact that the capitalist class ceased to remain in defensive lines and initiated a counter-attack that further consolidated its hegemony.
Keywords: Labor unions -- Turkey.; Labor unions -- Turkey -- History.